Interconnected grid protection systems - reference grid for testing an adaptive protection scheme - Lorz, Tobias; Jäger, Johann; Selimaj, Antigona; Hacker, Immanuel; Ulbig, Andreas; Heckel, Jan Peter; Becker, Christian; Dahlmanns, Markus; Fink, Ina Berenice; Wehrle, Klaus; Erichsen, Gerrit; Schindler, Michael; et al. (27th International Conference on Electricity Distribution (CIRED 2023), 2023)
The German power system is facing a continuous increase of volatile, decentralized power supplies from renewable energies. Growing loads from the mobility sector will increase the strain on the power grids even further. Faced with these rising challenges, current protection systems for distribution grids will likely encounter difficulties to provide the same level of security and dependability as they are often designed for a static grid protection with unidirectional power flow. This paper provides a reference grid for detailed study of protection behaviour based on real-world challenges encountered by German distribution grid operators. The grid consists of a 110kV high-voltage system and a 20kV medium-voltage system, which both are dominated by DER installations and a divergence between generation and load centres. The grid models were developed in close coordination with DSOs and provide a facility to operate in specific scenarios, that could be utilised in future grid operations.
CRIS-Team Scopus Importer:2024-12-16